How Persistent Are Shocks to World Commodity Prices? - Liang, Hong (IMF Working Papers; Working Paper ;, 1999)
This paper examines the persistence of shocks to world commodity prices, using monthly IMF data on primary commodities between 1957-98. We find that shocks to commodity prices are typically long-lasting and the variability of the persistence of price shocks is quite wide. The paper also discusses the implications of these findings for national and international schemes to stabilize earnings from commodity exports and finds that if price shocks are long-lived, then the cost of stabilization schemes will likely exceed any associated smoothing benefits.